5C.05: DIFFERENCES IN PREVALENCE, AWARENESS, TREATMENT AND CONTROL RATES OF HYPERTENSION BETWEEN MALE AND FEMALE. (June 2015) - Jardim, T.; Neiva, T.; Rodrigues, R.; Arantes, A.; Barros, C.; Chinem, B.; Rocha, R.; Euzébio, M.; Souza, W.; Araújo, Y.; Sousa, A.; Ressurreição, L.; et al.
Abstract : Objective: To compare differences in prevalence rates, awareness, treatment and control of hypertension between male and female workers of a public university in the Midwest region of Brazil. Design and method: Cross-sectional study with a representative sample of employers from the Federal University of Goias - Brazil. Data were collected in the workplace with individual questionnaire and measurement of casual blood pressure using semi-automatic devices (OMRON HEM model 711). Individuals using anti-hypertensive drugs and/or with blood pressure (BP) greater than or equal to 140/90mmHg (or 130/80mmHg, in the case of diabetics) were considered hypertensive. The knowledge about the disease was identified among those who claimed to be aware of the diagnosis before the measurements, and the treatment rate was calculated with those who reported using antihypertensive drugs. Controlled blood pressure was considered in individuals with values lower than 140/90mmHg (or 130/80mmHg, in the case of diabetics). The study was approved by the Ethics Committee of the institution. Results: The study included 1000 individuals with a mean age of 42.3 years (± 12.1); 393 (39.3%) patients were male. The prevalence of hypertension was 30.1% (n = 301), being higher among men (34.6%) than women (27.2%) (p < 0.05), aged over 50 years (p < = 0.001) and among those who have also referred hypertensive parents (p < 0.05). Among the hypertensive men 62.5% knew the diagnosis, 82.4% of those were under treatment, and 60.0% of those had BP under control. Among the hypertensive women 83, 6% knew the diagnosis, 90, 6% were under treatment and 79, 4% were with controlled BP (p < 0, 05 for the three variables). Conclusions: Despite the higher prevalence of hypertension in men, women had a greater knowledge of the diagnosis, higher rates of treatment and control of the disease in a population of workers from a Brazilian public university.